Jesus tradition, early Christian memory, and gospel writing: the long search for the authentic source - Kirk, Alan (Wm. B. Eerdmans Publishing Co., 2023)
Intro -- Title Page -- Copyright -- Dedication -- Contents -- List of Abbreviations -- 1. Written Gospel or Oral?: Lessing, Herder, and the Road to Strauss -- 2. Tendenzkritik: Drifting Back to Mark -- 3. Finding Jesus in the Two Document Hypothesis: Holtzmann to Wernle -- 4. Form Criticism: A Copernican Revolution? -- 5. The Farrer Juggernaut: Is It Unstoppable? -- 6. The Primitive Community Reborn: The "Galilean Q People" -- Bibliography.